Padrões e processos espaço-temporais da diversidade taxonômica e funcional de peixes de recifes rochosos de duas ilhas costeiras em área marinha protegida, sudeste do Brasil - Carminatto, Amanda Aparecida (2024)
In Brazil, most studies tend to focus on fish communities during the day and specific seasons. However, this approach overlooks temporal variations, such as the seasonal and diurnal cycles. Considering these variations is essential to understand the dynamics and adaptation of reef fish, especially in Marine Protected Areas (MPAs). Environmental conditions and ecological interactions have the potential to shape species distribution patterns. Ecomorphological attributes are often employed to assess the functional diversity of fish, with studies in this area if morphological variation leads to functional and performance differences resulting in resource usage disparities. Given the importance of comprehensively assessing the structure of rocky reef fish communities in MPAs exposed to seasonal and diurnal variations, this thesis aimed to explore spatial and temporal variations in fish communities, considering different aspects of taxonomic and functional diversity. Specifically, the study sought to (i) characterize the composition and similarity of fish fauna in the rocky reefs of Ilha Anchieta State Park (PEIA) and Ilha do Mar Virado (IMV) on the northern coast of SP, based on seasonal, diurnal, temperature, and depth variations; (ii) understand the spatial-temporal patterns and processes of fish richness and abundance on these islands across environmental gradients, assess whether the abundance distribution pattern remains the same for schooling and non-schooling species, and evaluate the effect of fishing restriction polygons for conservation and target species; (iii) characterize the reef fish occupation in different microhabitats of rocky reefs and investigate whether ecomorphological attributes explain this occupation. The study was conducted on two coastal islands in southeastern Brazil using images generated by a remotely operated vehicle (ROV) during the seasonal cycle of 2022 and samplings during day and night. A total of 16,661 individuals belonging to 81 species, 2 classes, 21 orders, and 38 families were observed. Significant differences in species composition and abundance were found among islands, climatic seasons, diurnal periods, and depth levels. The study emphasizes the importance of nocturnal research, considering the influence of artificial light on fish behavior. Significant factors explaining total numerical abundance and abundance of schooling and non-schooling species included islands, diurnal period, climatic season, depth, temperature, and the interaction between islands and depth, with the addition of interaction between specific factors in each behavior. Factors significant for explaining richness were the diurnal period, interaction between islands, and the diurnal period and Michaelis-Menten model parameters. The composition and occurrence proportion of target fishing species were influenced by the island factor, while conservation target species occurred randomly, regardless of the island. Ecomorphological attributes explained approximately 35% of the variation in species abundance in microhabitats. The results highlight the importance of habitat diversity in generating distinct morphological and functional adaptations in reef fish. Additionally, they indicate that rocky reefs in MPAs offer opportunities for ecomorphological diversification, influencing the dynamics and composition of fish communities. This study provides valuable insights into the dynamics of reef fish communities, emphasizing the significance of environmental and anthropogenic factors in their structure and composition. These findings can guide conservation and management strategies to preserve marine biodiversity in protected areas.